2005
DOI: 10.1007/s00415-005-0785-0
|View full text |Cite
|
Sign up to set email alerts
|

Perception of sleep: Subjective versus objective sleep parameters in patients with Parkinson’s disease in comparison with healthy elderly controls

Abstract: In summary, patients with PD have subjectively and objectively disturbed sleep as compared to healthy controls of the same age. However, they may not rate this poor sleep as much changed from their baseline sleep at home, and they have more somatic complaints. Increasing sleep efficiency might be of importance in PD patients, as it shows an association with subjective quality of time awake in the morning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 35 publications
(39 reference statements)
6
40
0
2
Order By: Relevance
“…Motor dysfunction was not improved by the use of melatonin [Medeiros et al 2007]. Although undetected differences in motor scores and PSG findings may have been due to the small sample size and a type II error, it must be noted that a significant divergence between PSG and subjective sleep evaluation had been reported in PD patients [Happe et al 2005]. The findings that subjective more than objective findings of impaired sleep quality have a greater negative impact on life quality [Means et al 2003] further suggest that PSG procedures may not be the best method for evaluating sleep disturbance in PD.…”
Section: Melatonin As a Therapeutic Agent In Parkinson's Diseasementioning
confidence: 89%
“…Motor dysfunction was not improved by the use of melatonin [Medeiros et al 2007]. Although undetected differences in motor scores and PSG findings may have been due to the small sample size and a type II error, it must be noted that a significant divergence between PSG and subjective sleep evaluation had been reported in PD patients [Happe et al 2005]. The findings that subjective more than objective findings of impaired sleep quality have a greater negative impact on life quality [Means et al 2003] further suggest that PSG procedures may not be the best method for evaluating sleep disturbance in PD.…”
Section: Melatonin As a Therapeutic Agent In Parkinson's Diseasementioning
confidence: 89%
“…The scoring of PSG in patients with IPD is a demanding task, as disease-inherent sleep fragmentation, abrupt sleep-wakefulness transitions, and further electroencephalographic abnormalities may occur. [42][43][44][45][46] However, in the current study automatic pattern recognition had always to be confirmed by manual scoring, based on the long experience of this sleep laboratory in patients with IPD. 47 In addition to reduced REM density, there may also be reduced mean amplitude of the eye movements in patients with IPD.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,[9][10][11] The percentage represents the difference between average subjective and objective total sleep time (TST). …”
Section: Methodsmentioning
confidence: 99%
“…4 Sleep misperception is most often experienced as wakefulness when the patient has been sleeping, but it can also be experienced as sleeping when the patient has been awake, the latter, with rare exception, in patients without neurological illnesses. [5][6][7][8] To date, there has been no report of sleep perception in multiple sclerosis (MS) patients.…”
Section: Introductionmentioning
confidence: 99%